General practice trainees’ understanding of post-sexual assault care: the impact of a specialist educational intervention - Kane, Daniel; Kennedy, Kieran M.; Flood, Karen; Eogan, Maeve (Irish journal of medical science, 2024)
Background Sexual assault (SA) is a highly prevalent issue, with significant adverse health sequelae. Given that general practitioners (GPs) may serve as the first point of contact for many SA victims, their awareness of post-SA care and appropriate understanding of referral pathways to a sexual assault treatment unit (SATU) are critically important. This study evaluated GP trainees’ knowledge of and comfort with post-SA care. Methods Educational intervention study using a didactic teaching session was delivered by a specialist forensic examiner on post-SA care. A pre and post-study questionnaire was implemented to assess participants’ knowledge and comfort levels with subject material. Significance was set at p -value below 0.05. Results Seventy-five GP-trainees attended the teaching session. Fifty-three completed the pre-teaching questionnaire and 50 completed the post-teaching questionnaire. Only a minority of trainees had received prior teaching in post-SA care as a medical student (13.2% n = 7) or as a postgraduate (28.3% n = 15). After the teaching session, there was a significant improvement trainees’ comfort levels in explaining a forensic examination ( p < 0.0001), referral pathways to a SATU ( p < 0.0001) and offering advice in relation to emergency contraception ( p < 0.0001). There was also a significant improvement in understanding HIV post-exposure prophylaxis (PEP) ( p < 0.001) and forensic examination (FE) time-lines ( p < 0.001). Conclusion This study reveals that GP-trainees have had limited exposure to teaching on post-SA care. Additionally, significant improvements were observed following a 1-h didactic teaching session on post-SA care. Trainees demonstrated increased understanding of SATU referral pathways, understanding of immediate medical care after SA, including PEP and FE timelines.